2015
DOI: 10.3758/s13428-015-0613-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of photo naming: Dutch norms for 327 photos

Abstract: In the present study, we report naming latencies and norms for 327 photos of objects in Dutch. We provide norms for eight psycholinguistic variables: age of acquisition, familiarity, imageability, image agreement, objective and subjective visual complexity, word frequency, word length in syllables and letters, and name agreement. Furthermore, multiple regression analyses revealed that the significant predictors of photo-naming latencies were name agreement, word frequency, imageability, and image agreement. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…Manuscript to be reviewed complexity (Shao & Stiegert, 2016). Our results indicate that children subjectively rated the picture format to be more complex, a format that objectively incorporates more visual details.…”
Section: Methodsmentioning
confidence: 75%
“…Manuscript to be reviewed complexity (Shao & Stiegert, 2016). Our results indicate that children subjectively rated the picture format to be more complex, a format that objectively incorporates more visual details.…”
Section: Methodsmentioning
confidence: 75%
“…We believe that the results of this study have several implications for the selection of Manuscript to be reviewed When children are exposed to simple drawings, they gather the typical salient elements of the object that help to develop figurative representations, flexibility of cognitive representation, and symbolic capacity during childhood (Simcock & DeLoache, 2006). This format also has less visual complexity, which could facilitate visual processing and influence naming latencies (Shao & Stiegert, 2016) whilst also having the added benefit of substantially reducing printing costs compared with colored photographs. On the other hand, colored photographs can facilitate object naming and provide ecological stimuli that allow specific transference to objects.…”
Section: Discussionmentioning
confidence: 99%
“…A pioneering normative study is the one reported by Snodgrass and Vanderwart (1980). This consisted of 260 black-and-white line drawings with norms for name agreement, image agreement (or the degree of agreement between the mental Brodeur, Dionne-Dostie, Montreuil, & Lepage, 2010;and Brodeur, Guérard, & Bouras, 2014;in English and French;Saryazdi, Bannon, Rodrigues, Klammer, & Chambers, 2018;in Turkish;Shao & Stiegert, 2016;in Dutch;Moreno-Martínez & Montoro, 2012;in Spanish;Navarrete, Arcara, Mondini, & Penolazzi, 2019;in Italian). Thus, the need for more ecological stimuli than those provided by line drawings has begun to be highlighted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other photographic datasets with norms for adults are the set published by Viggiano et al [ 43 ], in English and Italian; the Hatfield Image Test [ 46 ], in English; the C.A.R.E. set [ 47 ] in English; the set of Shao & Stiegert [ 48 ] in Dutch; the set of Saryazdi, Bannon, Rodrigues, Klammer, & Chambers [ 49 ], in Turkish. The ecological version of the Snodgrass and Vanderwart [ 3 ] set [ 42 ] is the only one in Spanish, and has recently been published also in Italian [ 50 ].…”
Section: Introductionmentioning
confidence: 99%